Molecular screening of pathogenic Escherichia coli strains isolated from dairy neonatal calves in Cordoba province, Argentina - Picco, Natalia Yanina (2015)
The aim of this study was to perform a current molecular characterization of bovine pathogenic Escherichia coli strains isolated from random samplings in Argentinean dairy farms. Rectal swabs were obtained from 395 (63.7 %) healthy and 225 (36.3 %) diarrheic calves, belonging to 45 dairy farms in Cordoba Province, Argentina. E. coli isolates were examined for virulence genes (f5, f41, f17, sta, stb, lt, eae, vt) using PCR and the prevalence of E. coli virulence profiles was spatially described in terms of spatial distribution. A total of 30.1 % isolates were found to be positive for at least one of the virulence genes. Depending on the different gene combinations present, 11 virulence profiles were found. Most of the isolates analyzed had a single gene, and no combination of fimbrial and enterotoxin gene was predominant. There was no association between the frequency and distribution of E. coli virulence genes and calf health status. Most of the virulence profiles were compatible with ETEC strains and showed a homogeneous distribution over the sampled area. A clustering pattern for E. coli virulence profiles could not be recognized. This work provides updated information on the molecular characterization of pathogenic E. coli strains from dairy herds in Cordoba, Argentina. These findings would be important to formulate prevention programs and effective therapies for diarrhea in calves caused by E. coli.